(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2021)
There are various economic indicators that demonstrate the strength or weakness of a country’s economic condition and Gross Domestic Product is one of them, with capital market turnover contributing significantly to GDP. The broad objective of the study is to show an analysis of the importance of research and development of capital market of Bangladesh. And also is to provide identify the investors perception about the research and development of capital market of Bangladesh and give some recommendations and strategic insight to improve the quality research to contribute on future development of the capital market of Bangladesh. Moreover, How Capital Market Research will help to improve the capital market growth, finding new opportunities, diversifying market products and segmentations, improving Market efficiency, attracting foreign investment, increasing liquidity as well as making investment decisions. The research is based on a structured questionnaire survey procedure. The findings revealed that investors are interested in investing in the secondary market with lack of enough knowledge, confidence and market expertise.